2021
DOI: 10.24198/jkrk.v3i1.32143
|View full text |Cite
|
Sign up to set email alerts
|

Peran Orang Tua Dalam Mendampingi Anak Menggunakan Media Sosial Di Tengah Pandemi Covid-19

Abstract: ABSTRAKSejak pertama kali terdeteksi muncul di Kota Wuhan, Tiongkok, pandemi Virus Corona (Covid-19) telah membuat kepanikan dimana-mana, ratusan ribu manusia terinfeksi dan ribuan lainnya meninggal dunia akibat dari pandemi ini. Untuk mengantisipasi dampak pandemi yang lebih besar pemerintah mengkampanyekan kepada masyarakat agar lebih sering berkegiatan di dalam rumah untuk memutus rantai penyebaran virus corona. Situasi tersebut memaksa segala bentuk aktifitas seperti pekerjaan dan pendidikan dilaksanakan d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
7

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 0 publications
0
6
0
7
Order By: Relevance
“…[4] States that the family is seen from its function, namely having the duty and function of care, emotional and material support, and fulfilling certain roles. In line with this, Muchtar [5] revealed that the family is an important part of the community unit. The family has an important role in caring for, educating, protecting and nurturing children.…”
Section: Introductionmentioning
confidence: 78%
“…[4] States that the family is seen from its function, namely having the duty and function of care, emotional and material support, and fulfilling certain roles. In line with this, Muchtar [5] revealed that the family is an important part of the community unit. The family has an important role in caring for, educating, protecting and nurturing children.…”
Section: Introductionmentioning
confidence: 78%
“…Then the learning solution at school was replaced with online learning or familiarly called online, to anticipate the spread of Covid-19 (P.A Chusna & A.D. M Utami, 2020;Asmawati, 2021;Zahara, Mulyana, and Darwis, 2021). The role of parents in introducing and using ICT as a means of online learning media is a directive from teachers based on orders from the central government and then forwarded by local governments to close schools.…”
Section: B Discussionmentioning
confidence: 99%
“…The role of parents in introducing and using ICT as a means of online learning media is a directive from teachers based on orders from the central government and then forwarded by local governments to close schools. (Asmawati, 2021;P.A Chusna & A.D.M Utami, 2020;Zahara et al, 2021)Because of this order, schools and parents must introduce ICT to children.…”
Section: B Discussionmentioning
confidence: 99%
“…Peran orang tua sebagai penanggung jawab anak adalah bentuk perlindungan kepada anakanaknya (Zahara, S., et al, 2021). Kehadiran dan keterlibatan orang tua penting dalam hal ini, Orangtua yang bersama-sama dengan anak untuk berinteraksi dengan video secara tidak langsung akan merangsang audio visual anak dengan komplek (Wulandari,H., et al, 2021).…”
Section: Pendahuluanunclassified